Beta-glucan enhances the response to SVCV infection in zebrafish. (July 2018) - M. Medina-Gali, Regla; Ortega-Villaizan, María del Mar; Mercado, Luis; Novoa, Beatriz; Coll, Julio; Perez, Luis
Abstract: The antiviral effects of beta-glucan, an immunostimulatory agent were studied in zebrafish both in vitro and in vivo . Here we show that zebrafish ZF4 cells as well as whole fish primed with yeast β-glucan zymosan exhibited increased cytokine expression and elevated response to spring viremia of carp virus (SVCV) infection. In vitro, previous treatment of β-glucan enhanced ZF4 cell viability against SVCV infection which is associated to the activation of interferon signaling pathway and inflammatory cytokines gene expression. In vivo, the SVCV-infected fish primed with β-glucan had a higher survival rate (≈73%) than the control SVCV-infected group (≈33%). Additionally, up-regulation of the expression of a set of genes involved in innate immune response was detected in zebrafish intraperitoneally injected of β-glucan: il1b, il6, il8, il10 and tnfa transcripts showed increased expression that appear to be rapid (2 days) but not long-lived (less than 2 weeks). The present study is, to our knowledge, the first to combine cell culture and in vivo approaches to describe host response to β-glucan stimulation and viral infection in zebrafish. Highlights: Yeast β-glucan zymosan is a potent immunostimulant in D. rerio both in vitro and in vivo. ZF4 cells exposed to β-glucan exhibited protection against SVCV infection. β-glucan i.p. injection into zebrafish enhances resistance to SVCV challenge two weeks after glucan administration. Up-regulation of host antiviral genes gig2, ifnphi1, il1b, il6, il8 and il10 by β-glucan was observed in zebrafish.